Pemberdayaan Pemuda Gereja Dalam Melaksanakan Bimbingan Belajar Di Desa Tano Tombangan - Saragi, Dame Ria Rananta; Sianipar, Lasma Lenida Rosinta; Samosir, Anita Tresia (Universitas Negeri Gorontalo, 2025)
In community service activities with the aim of fulfilling obligations to be useful to the community, the empowerment of HKBP Panabari Church Youth in Tano Tombangan Village, South Tapanuli in carrying out reading, writing and arithmetic tutoring for Sunday school children in Tano Tombangan Village is effectively able to enable Sunday school children to read, write and count. The method of implementing this service is carried out systematically and is divided into several activities. This activity was held October 20 to December 20. The youth of the HKBP Panabari Church have high intentions in teaching Sunday school children and have very good enthusiasm in following guidance, however, there are obstacles in this service, namely the lack of parental motivation for children to follow guidance, especially when there are traditional events, parents prefer to take their children to traditional events rather than taking guidance to learn reading, writing and arithmetic.